2009
DOI: 10.1002/eat.20701
|View full text |Cite
|
Sign up to set email alerts
|

Medical futility and psychiatry: Palliative care and hospice care as a last resort in the treatment of refractory anorexia nervosa

Abstract: Objective: The concept of medical futility is accepted in general medicine, yet little attention has been paid to its application in psychiatry. We explore how medical futility and principles of palliation may contribute to the management of treatment refractory anorexia nervosa. Method:We review the case of a 30-year-old woman with chronic anorexia nervosa, treated unsuccessfully for several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 17 publications
0
62
0
5
Order By: Relevance
“…Research utilising both quantitative and qualitative methods have identified the importance and need for a consistent definition and clear criteria for identifying patients within this subgroup (Arkell & Robinson, 2008;Long, Fitzgerald, & Hollin, 2012;Lopez, Yager, & Feinstein, 2010;Meerman & Vandereycken, 1985). A literature review by Wonderlich et al (2012) highlighted the lack of a definition regarding chronicity in the published literature and proposed that despite treatment options being investigated for this subgroup, findings are severely limited due to the lack of a coherent definition.…”
Section: Ered the Diagnostic And Statistical Manual Of Mental Healthmentioning
confidence: 99%
“…Research utilising both quantitative and qualitative methods have identified the importance and need for a consistent definition and clear criteria for identifying patients within this subgroup (Arkell & Robinson, 2008;Long, Fitzgerald, & Hollin, 2012;Lopez, Yager, & Feinstein, 2010;Meerman & Vandereycken, 1985). A literature review by Wonderlich et al (2012) highlighted the lack of a definition regarding chronicity in the published literature and proposed that despite treatment options being investigated for this subgroup, findings are severely limited due to the lack of a coherent definition.…”
Section: Ered the Diagnostic And Statistical Manual Of Mental Healthmentioning
confidence: 99%
“…Además de la información habitual sobre la técnica de la ECP, los pacientes deben ser informados de la posibilidad de riesgos desconocidos asociados al perfil específico de los pacientes y a la diana quirúrgica. También es preciso clarificar que el tratamiento podría no producir ningún beneficio, y que un segundo procedimiento para extraer el sistema podría ser necesario en caso de fracaso, con los consiguientes riesgos asociados No existen criterios claros respecto a la resistencia a tratamientos conservadores, pero este tema está cada vez más en auge, considerándose incluso tratamiento paliativo para aquellas pacientes en las que no se produce mejoría tras varios años de tratamiento conservador (50).…”
Section: Consideraciones éTicasunclassified
“…"Mickey" Stunkard, whose research (Stunkard et al, 1986) refuted psychodynamic models of eating behavior and who introduced into the field clinical presentations we now recognized as binge-eating disorder (BED) or night-eating syndrome (Stunkard & Allison, 2003;Stunkard, Grace, & Wolff, 1955). Four inaugural members still serve on our board, enriching the IJED by bringing to their reviewer role a valuable historical perspective and extensive knowledge of the field and, as IJED authors, by expanding our knowledge base (referenced in the following sentence are their most cited publication and their most recent IJED publication): W. Stewart Agras (Kraemer, Wilson, Fairburn, & Agras, 2002;Lock et al, 2016), Katherine Halmi (Halmi, Falk, & Schwartz, 1981;Mahr et al, 2015), Michael Strober (Khalsa et al, 2015;Strober, Freeman, & Morrell, 1997), and Joel Yager (Gwirtsman, Roybyrne, Yager, & Gerner, 1983;Lopez, Yager, & Feinstein, 2010).…”
Section: Scientific Leadershipmentioning
confidence: 99%